C++ for engineers and scientists - Bronson, Gary J.; Borse, G. J. (Garold J.) (Boston: Thomson Course Technology., 2010)
'Now in its third edition, Bronson's C++ for Engineers and Scientists makes C++ accessible to first-level engineering students as C++ maintains its stronghold in engineering and scientific communities. The text continues to take a pragmatic approach that incorporates actual engineering and science problems for its applications and examples. Students begin with a foundation in procedural programming, moving into object-oriented concepts in the second half of the text. This new edition also offers new case studies and an expanded selection of examples from a variety of fields including thermodynamics, optics, and fluid mechanics. All chapters include extensive opportunity for practice through end-of-section and end-of-chapter exercises and programming projects.'--Publisher's description.
Preliminaries -- Problem solving using C++ -- Assignment, formatting, and interactive input -- Selection structures -- Repetition statements -- Modularity using functions -- Arrays -- I/O streams and data files -- Completing the basics -- Introduction to classes -- Class functions and conversions -- Pointers -- Structures -- Numerical methods -- Bit operations.
Includes index.
Keywords: C++ (Computer program language